Cuttings transportation in coiled tubing drilling for mineral exploration - Kamyab, Mohammadreza (Curtin University, 2014)
Cuttings transportation in micro-borehole annulus in coiled tubing drilling for mineral exploration was studied. The effect of cuttings size and mud properties as well as hole inclination was simulated physically using a flow loop. Computational fluid dynamics was applied to simulate lab experiments and do sensitivity analysis of various parameters. The results show significant differences in cuttings transport response in mineral exploration comparing to the oil and gas drilling applications.